Gelation of siloxane-poly(oxypropylene) composites - Sarmento, VHV; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2002)
The viscoelastic properties of siloxane-poly(oxypropylene) (PPO) nanocomposites prepared by the sol-gel process has been analyzed during gelation by dynamic rheological measurements. The changes of storage and loss moduli, complex viscosity and phase angle has been measured as a function of time showing the newtonian viscosity of the sol in the initial step of gelation, and its progressive transformation to a viscoelastic gel. The rheologic properties have been correlated to mass fractal, nearly linear growth models and percolation theory. This study, completed by quasi-elastic light scattering and Si-29 solid state nuclear magnetic resonance measurements, shows that the mechanisms of gelation of siloxane-PPO hybrids depend on the molecular weight of the polymer and on the pH of the hybrid sol. For hybrids prepared in acid medium, a polymerization involving silicon reactive species located at the extremity of the polymer chains and presenting a functionality f = 2 occurs, forming a fractal structure during the first stage of sol-gel transition. For samples prepared under neutral pH, the fractal growth is only observed for hybrids containing short polymer chains (M-w similar to 130 gmol(-1)). The fractal dimensionality determined from the change in the rheological properties, indicates that the fractal growth mechanism changes from reaction-limited to diffusion-limited aggregation when the molecular weight of the PPO increases from 130 to 4000 gmol(-1) and as catalyst conditions change from acidic to neutral. Near the gel point, these hybrid gels have the typical scaling behavior expected from percolation theory. (C) 2002 Elsevier B.V. B.V. All rights reserved.